Engajamento de stakeholders: bibliometria, revisão sistemática e desenvolvimento de um instrumento de mensuração no turismo - Fassione, Gustavo Henrique da Silva (2020)
Stakeholders are protagonists in the development of tourism, playing important roles in the success of a tourist destination. In this research, the engagement promoted by the destination management organization (DMO) to the stakeholders offering tourism was considered. In order to analyze the development of studies on stakeholder engagement and validate a scale of this theme in tourism, three interdependent studies were proposed. In the first study, we sought to know the bases and trends of studies on stakeholder engagement. In the second study, the connection between the practice of stakeholder engagement and competitiveness was investigated. Finally, in the third study, a scale originally developed in the context of health was adapted and validated in the context of tourism. As main results, the first study found the importance of stakeholder theory, dialogue with stakeholders, their role in organizational performance and the development of environmental strategies, which served as a basis for studies on stakeholder engagement. In addition, it was found that the main trends in studies on the topic take into account the network relationship between stakeholders and the focus on communication, value creation and sustainable development. The second study reinforced some forms of stakeholder engagement, in addition to highlighting the predominance of studies that connect engagement to competitiveness developed in the context of tourism. Finally, the third study validated a scale of engagement of stakeholders in tourism, whose practice is promoted by the destination management organization. After the validation steps, four dimensions were reached that make up the engagement construct. They are: Partnership; Consideration; Relationship with the DMO; and Knowledge transfer. Therefore, a validated measuring instrument was obtained. At the end of this research, limitations and suggestions for future studies were reported.